Corporate governance, Executive Compensation and Firm Performance - Kabir, Md Awal Al (2018)
The study is conducted to analyse the impact of corporate governance on firm performance from the period of 2000 to 2006. Here G index is used as a measure of corporate governance and ROA, ROE, and Tobin’s Q are use to measure the firm performance. Samples are taken those firms which are used by Gompers, Ishii, and Metrick in their study to measure the corporate governance and stock price. On the other hand firm performance is also measure on the basis of executive compensation which is burning issue of corporate governance now a days. Here S&P 500 and 600 firms are considered to investigates the impact of executive compensation over firm performance for the period of 2008 to 2017. Firm performance is measure on the basis of ROA, ROE and Market to book ratio. Here executive compensation is considered only CEO overall compensation e.g current compensation and future incentives. In this study financial firms are excluded due to different nature of accounting systems. Along with descriptive analysis correlation matrix and regressions are conducted for these panel data. A big problem was endogeneity which is also addressed here to make the models acceptable. This study does not get any significant relationship between corporate governance and firm performance. The model describes very insignificant value of r square. On the other we also do not get any signifiant impact of executive compensation over firm performance as well both for large and small capital firm. That means executive compensation is important determinant of performance whether in giant firms or small organisation.